Pengembangan E-modul Interaktif Mata Pelajaran Project Kreatif dan Kewirausahaan Kelas XI Program Keahlian Desain Komunikasi Visual - Angraini, Novita; Irsyadunas, Irsyadunas; Junaidi, Satrio (Unversitas Muhammadiyah Mataram, 2024)
Abstract: The aim of this research was to produce an interactive e-module in packaging and product design material at SMK Negeri 1 Guguk class XI Visual Communication Design Skills Program in Creative Project and Entrepreneurship subjects. This research uses the Research and Development method with the development model used in this research being the ADDIE model. The subjects involved in the Creative Project and Entrepreneurship subjects in the 2023/2024 academic year amounted to 29 students and 3 teachers. This research instrument is a validity instrument using a validity questionnaire with 4 validators. The validity assessment includes 3 people as media expert validators and 1 person as material expert validator. Based on the media validity results, validation results were obtained at 84.35% in the